Numerical conformal mapping via the Bergman kernel - Razali, M. R. M.; Nashed, M. Z.; Murid, A. H. M. (Elsevier Science B.V., 1997)
A new method to compute the Riemann mapping function via the Bergman kernel is presented. The method expresses the Bergman kernel as the solution of a second-kind integral equation involving the Neumann kernel. For symmetric regions, the integral equation can be transformed into a new one that uses only a small part of the original boundary. Numerical implementations on some test regions are also presented